Knowledge, attitudes, and practices regarding vector-borne diseases in central Mexico - Joel E. Nava-Doctor; César A. Sandoval-Ruiz; Antonio Fernández-Crispín (BMC, 2021)
Abstract Background While vector-borne diseases (VBDs) pose an important public health problem worldwide, there is a limited and conflicting knowledge about such illnesses in rural or urban settings. The present study aimed to explore the social representations (SRs) held by people in the state of Puebla, Mexico on insects and the diseases they transmit. Understood as the group of ideas held and shared by a group of human beings which enable them to understand and interpret the world, SRs constitute what could be called a collective science or knowledge of everyday life. Methods The present study was conducted in six municipalities in the state of Puebla, wherein an open-ended questionnaire was applied with three age ranges. A total of 360 questionnaires were applied with people dedicated to a variety of activities. The survey data was analyzed to identify the SR's structure (the central nucleus of the SR and its peripheral system) and the level of organization in order to explore the degree to which the ideas that constitute it are shared and based on consensus. To describe the structure of the SR, a network analysis was conducted and complemented by a correspondence analysis, which also enables the differences between social groups to be identified. Results Popular knowledge on insects and VBDs is often limited, even in communities in which more than one-vector insect is found. The elements that were most frequently mentioned in the data, as pertaining to the insect-disease relationship, were mosquitoes and dengue fever, with scorpions (which are arachnids and not insects) receiving the second-highest number of mentions, while other insects such as kissing bugs, flies, and cockroaches were also mentioned as transmitting VBDs. While television was the main information source on VBDs for the residents of these communities, biology books were also mentioned. Chemical control measures (insect repellents) were the most used prevention method, and traditional medicine was the remedy most commonly used to treat insect bites and transmitted diseases. Entomophobia was the main cause for the respondents' fear and rejection of insects. Beyond the deleterious effects of many insects, those surveyed also recognized a positive relationship with insects due to economic and nutritional benefits they provide. Conclusions The present study provides relevant information on how insects and the diseases they transmit are perceived by rural and urban communities. Although the population is aware of dengue fever and the role of mosquitoes in transmitting it, information campaigns are required for other historically neglected VBDs, such as leishmaniasis, Chagas disease, and, even, rickettsiosis. As it is important to understand the impact that these illnesses have on communities further research is required to ensure that better information and guidance is provided on VBDs in order to develop a culture of illness prevention in not only the rural but also the metropolitan communities of the state of Puebla.